(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The impositions expressed by a given society, reflected in the way of acting, thinking and feeling, which are markedly external to the individual, can exert an imperative and coercive power of society over them. Such a perspective has been observed in homeless people (HP). This research aims at a reflective analysis of Physical Education, in its pedagogical and sociocultural perspective of the body in movement, based on the understanding of HP in the light of the "social fact". The studies that guided the research were based on: historical and sociocultural evidence of the body in society; pedagogical aspects of physical education; and the social relationships built by the HP. The study used direct observation and elaboration of scripts. Exploratory data collection was carried out, through readings and analysis of the social context in which the activities and observations would be carried out in a practical context. The proposed activity was Capoeira, as it is a cultural manifestation that came closer to the historical and cultural relations of construction of Brazilian identity. The assigned pedagogical action was based on procedural, conceptual and attitudinal components. Despite a varied motor repertoire, in light of the “social fact”, it was observed that HP are not even perceived by society. In this context, a rupture of cultural identity associated with self-image, shaken self-esteem and difficulty in self-affirmation stands out. This is reflected as a central point for the social integration of the HP. There was a need for a broader debate on the possibilities of stimulating a space for “listening” during classes; indirectly insert attitudinal and conceptual aspects through body expressions and music as a way of working on the self-image of the studied PSR.